Development of Kilowatt-Hour Consumption Monitoring System for a State University: Real-Time Tracking with Sub-Meter - Angelo T. Aga; Jomer C. Basa; Tyrone Jr. M. Cailing; Jomar D. David; Adolfo E; Rimando VII; Charles Mendy D. Canonero; Andrei M. Viscayno (Universitas Komputer Indonesia, 2025)
This study details the development of an Internet of Things (IoT)-based kilowatt-hour (kWh) consumption monitoring system for Don Honorio Ventura State University. Utilizing smart sub-metering technology, the system captures real-time, granular electrical data at the building level, significantly overcoming the limitations of conventional utility meters. The integrated web-based dashboard effectively visualizes usage trends, historical consumption, and peak demand periods. Field testing in selected campus buildings confirmed the system's overall reliability, usability, and performance. Ultimately, this real-time monitoring solution enhances energy visibility, promotes cost-reduction efforts, and fosters sustainable, energy-efficient practices aligned with the university's broader smart campus initiatives